SOSIALISASI LITERASI DIGITAL QUR’ANI MELALUI PROGRAM ISTIQOMAH BERBASIS APLIKASI MOBILE DENGAN PENDEKATAN PARTICIPATORY LEARNING AND ACTION - Alazhari, Muhamad Roihan; Handoko, Bobi; Angella, Shelly; Yasriady, Dedy (LPPM Universitas Awal Bros, 2025)
In today's digital era, the habit of reading the Qur'an has significantly declined, especially among the younger generation. This is due to the dominance of digital activities such as social media, gaming, and other online entertainment. In response to this phenomenon, a community service team in collaboration with the Generasi Umat Terbaik Foundation (YGUT) conducted a Qur’anic literacy socialization program through the